The juridification of vulnerability in the European legal culture - Catanzariti, Mariavittoria (Oñati Socio-Legal Series, 2022)
Although not being a codified legal concept, vulnerability has been increasingly used over the past years in the reasoning of the European Court of Human Rights. Some relevant cases dealing with the multi-faceted notion of vulnerability are retrospectively presented to exemplify this trend, considering two aspects. First, the paper explores the process of juridification of vulnerability in the ECtHR’s case law from the perspective of the sociology of law. Through the emerging uncodified notion of vulnerability, it seeks to inquire the relationship of juridification and legal culture focusing on the legal response to social needs arising from the use of vulnerability. Second, the paper conceptualizes vulnerability looking at its interplay with different human rights’ violations. The paper ultimately aims to re-theorize the role of legal culture as a catalyst for juridification, taking vulnerable conditions and their relevance to the law as a paradigmatic example of social change.